Kajian Deskriptif-Komparatif Epistemologi Pendidikan Ibnu Khaldun dan Fazlur Rahman - Mustofa, Idam (JOIES (Journal of Islamic Education Studies), 2016)
Islamic education is potential in the formation of civil society and community-citizenship. Islamic education can be a critical educational vehicle for the people and relieve the lowest layers of society of ignorance, backwardness, helplessness and poverty. Here, Islamic education can become an important educational institution in foster of democratic values continuously through the process of democratization of education or democratic education. In some countries (Indonesia, Egypt, Iran, China, Brazil, United States) make great efforts to democratize education to strive continuously for implementation of democratic education. It is indeed a need for each country to reach a better situation for every citizen. The efforts of Synergize Islamic education, democratization and citizenship, should be done by making Islam as the source of values to build the character of the nation that creat Islamic education based on nationality.